The Impact of Employee Autonomy, Distributed Leadership, and Bottom-up Idea Generation on Perceived Innovation: A Case Study MEEQ - Selsabil CHEBBOUBA (Revista de Management Comparat International)
This study examines how employee autonomy, distributed leadership, and bottom-up idea generation influence innovation within MEEQ, a Japanese company balancing traditional corporate structures with modern innovation practices. Using a mixed-methods approach, data were collected through structured initial interview with the CEO, followed by employee questionnaire and semi-structured manager interviews. Results indicate that employee autonomy significantly contributes to perceived innovation outcomes, while distributed leadership and idea generation require stronger structural mechanisms to maximize their impact. Key barriers include communication gaps in reporting, limited participation in structured idea-sharing initiatives, and employees' hesitation to openly contribute innovative ideas. The findings highlight the critical role of autonomy and open communication in fostering innovation, offering insights into how Japanese companies can adapt Western innovation practices while navigating cultural constraints.